Genetically-encoded discovery of proteolytically stable bicyclic inhibitors for morphogen NODAL. Issue 28 (17th June 2021) - Wong, Jeffrey Y.-K.; Mukherjee, Raja; Miao, Jiayuan; Bilyk, Olena; Triana, Vivian; Miskolzie, Mark; Henninot, Antoine; Dwyer, John J.; Kharchenko, Serhii; Iampolska, Anna; Volochnyuk, Dmitriy M.; Lin, Yu-Shan; et al.
Abstract : A two-fold symmetric linchpin (TSL ) converts readily available phage-displayed disulfide peptide libraries to proteolytically stable bicyclic peptides. The bicyclic phage library was screened to discover an antagonist of NODAL morphogen. Abstract : In this manuscript, we developed a two-fold symmetric linchpin (TSL ) that converts readily available phage-displayed peptides libraries made of 20 common amino acids to genetically-encoded libraries of bicyclic peptides displayed on phage. TSL combines an aldehyde-reactive group and two thiol-reactive groups; it bridges two side chains of cysteine [C] with an N-terminal aldehyde group derived from the N-terminal serine [S], yielding a novel bicyclic topology that lacks a free N-terminus. Phage display libraries of SX1 CX2 X3 X4 X5 X6 X7 C sequences, where X is any amino acid but Cys, were converted to a library of bicyclic TSL -[S]X1 [C]X2 X3 X4 X5 X6 X7 [C] peptides in 45 ± 15% yield. Using this library and protein morphogen NODAL as a target, we discovered bicyclic macrocycles that specifically antagonize NODAL-induced signaling in cancer cells. At a 10 μM concentration, two discovered bicyclic peptides completely suppressed NODAL-induced phosphorylation of SMAD2 in P19 embryonic carcinoma cells. The TSL -[S]Y[C]KRAHKN[C] bicycle inhibited NODAL-induced proliferation of NODAL-TYK-nu ovarian carcinoma cells with apparent IC50 of 1 μM. The same bicycle at 10 μM concentration did not affect the growth of the control TYK-nu cells. TSL -bicycles remained stable over the course of the 72 hour-long assays in a serum-rich cell-culture medium. We further observed general stability in mouse serum and in a mixture of proteases (Pronase™) for 21 diverse bicyclic macrocycles of different ring sizes, amino acid sequences, and cross-linker geometries. TSL -constrained peptides to expand the previously reported repertoire of phage-displayed bicyclic architectures formed by cross-linking Cys side chains. We anticipate that it will aid the discovery of proteolytically stable bicyclic inhibitors for a variety of protein targets.